Katalog Naskah Dayah Tanoh Abee, Aceh Besar - Meij, Dick van der (Studia Islamika, 2010)
Book Review: Oman Fathurahman (main compiler), Aoyama Toru (main editor), and Arai Kazuhiro, Sugahara Yumi, and Salman Abdul Muthalib (editors), Katalog Naskah Dayah Tanoh Abee Aceh Besar. (Jakarta: Komunitas Bambu, Tokyo University of Foreign Studies [TUFS], Masyarakat Pernaskahan Nusantara [Manassa], PPIM UIN Jakarta, PKPM Aceh, Dayah Tanoh Abee, 2010), ISBN 979-3731-99-0, xxxiv + 374 pages.The book is enlivened by a number of photos of the people who were involved in the present project (scholarly speaking unnecessary, but charming as it gives some idea of the circumstances under which the information for this catalogue was gathered), of members of the family of the leaders of the dayah (especially Tgk. Muhammad Dahlan, beautifully portrayed by Henri Chambert-Loir on page xxv, sadly without an indication as to when the photo was taken), an early photo of members of the extended Tanoh Abee family showing a much younger Henri Chambert-Loir in probably 1976, a photo of Oman Fathurahman and Tgk.DOI: 10.15408/sdi.v17i3.456